Pemanfaatan Sistem Klasifikasi dan Otomasi di Perpustakaan Politeknik Internasional Bali - Callysta, Grimonia Alena; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Widya Sosiopolitika; Vol 7 No 1 (2025): ISU-ISU SOSIAL DAN POLITIK, 2025)
The development of information technology affects various fields of work, one of which is in the Library. The existence of an opensource system helps librarians in meeting The information needs of users. Classification and automation activities play an important role in supporting the optimization of library management. The use of classification and opensource systems in libraries needs to be supported by the competence of librarians. Currently, there are more and more developments in opensource applications and classification systems in the world of libraries, so there is a need for evaluation in the use of these systems. This study aims to find out the real implementation of the use of classification and automation systems in the Bali International Polytechnic Library. To see the application of the classification and automation system, the author uses a descriptive qualitative method, with data collection techniques through interviews and literature studies. The results of this study show that the Bali International Polytechnic Library is able to implement classification activities well using the e-DDC 23 classification system version 3.3 and the automation system in the form of Senayan Library Management (SLiMS) version 9 Bulian. The system has an optimal impact on the management of management activities, especially the retrieval of information at the Bali International Polytechnic Library.